(untitled) (Research, Society and Development, 2020)
It’s necessary to study the variability of soil compaction identified by the resistance to penetration, allowing handling at a variable rate with agricultural equipment before an adequate sampling grid. The aim of this study was to evaluate the spatial variability of resistance to penetration with different sampling grids and indication of management of an Oxisol. An experimental area of ​​0.2 ha and a 4 x 4 m sampling grid were used, totaling 120 readings of resistance to penetration. The average gravimetric soil moisture in the 0.0-0.2 m layer at the time of data collection was 43.5%. The data were submitted to statistical analysis, performed for different sampling intensities, simulated by the exclusion of sampling points uniformly distributed across the area, obtaining a 4 x 4 m, 4 x 8 m and 4 x 40 m sampling grid. The layer between the range of 0.05 and 0.2 m showed a higher mean of the penetration resistance values ​​in relation to the other studied layers. To perform motorized handling at a fixed rate throughout the area, the 4x40 mesh can be used. To perform handling at a variable rate, the ideal mesh is 4x4, being possible to use the 4x8 mesh.